Understanding of the importance of the spore coat structure and pigmentation in the Bacillus subtilis spore resistance to low-pressure plasma sterilization. (15th June 2016) - Raguse, Marina; Fiebrandt, Marcel; Denis, Benjamin; Stapelmann, Katharina; Eichenberger, Patrick; Driks, Adam; Eaton, Peter; Awakowicz, Peter; Moeller, Ralf
Abstract: Low-pressure plasmas have been evaluated for their potential in biomedical and defense purposes. The sterilizing effect of plasma can be attributed to several active agents, including (V)UV radiation, charged particles, radical species, neutral and excited atoms and molecules, and the electric field. Spores of Bacillus subtilis were used as a bioindicator and a genetic model system to study the sporicidal effects of low-pressure plasma decontamination. Wild-type spores, spores lacking the major protective coat layers (inner, outer, and crust), pigmentation-deficient spores or spore impaired in encasement (a late step in coat assembly) were systematically tested for their resistance to low-pressure argon, hydrogen, and oxygen plasmas with and without admixtures. We demonstrate that low-pressure plasma discharges of argon and oxygen discharges cause significant physical damage to spore surface structures as visualized by atomic force microscopy. Spore resistance to low-pressure plasma was primarily dependent on the presence of the inner, and outer spore coat layers as well as spore encasement, with minor or less importance of the crust and spore pigmentation, whereas spore inactivation itself was strongly influenced by the gas composition and operational settings.